GOING CONCERN UNTUK JANGKA PENDEK - Muhamad Rizky Wijaya (Journal Of Communication Education, 2018)
ABSTRACTThis research takes the issue of companies that experienced financial distress would lead to a conflict of interest between management and owners. This research to examine the influence of capital structure, the audit committee, managerial ownership and the size of the company's performance as well as view the company's going concern mediated by the agency cost.This type of research is testing the hypothesis with a type of explanatory-causality. Using a time horizon of one short study. The object of research is the use of a manufacturing company with a unit of industry analysis. Source data using secondary data. The research sample using purposive sampling. Data analysis using path analysis to test the two SLS.The results of this study indicate that capital structure and firm size affect the agency cost, the audit committee and managerial ownership does not affect the agency cost, agency cost does not affect the performance of the company, capital structure, the audit committee, managerial ownership and firm size does not affect the performance company, the company's performance affect the going concernThe research findings indicate that the size of the company is the most dominant factor affecting the agency cost, scope of large companies require substantial funding for operations of the company Keywords: Capital Structure, Audit Committee, Managerial ownership, Size, Agency cost, The Company's Performance, Going concern, Financial Distress